Transcatheter aortic valve replacement for aortic regurgitation secondary to aortic sinus dilation with incidentally detected aortic chordae tendineae: case report - Li, Lingli; Liu, Lulu; Bai, Wenjuan (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAortic chordae tendineae (ACT) are rare fibrous strands originating from early aortic valve cusp formation as embryonic remnants. Most aortic chordae tendineae are asymptomatic, but they may cause aortic regurgitation via chordal rupture or cusp restriction. This case presents transcatheter aortic valve replacement (TAVR) for aortic regurgitation secondary to aortic sinus dilation with incidentally detected ACT that did not directly contribute to valvular dysfunction.Patient presentationAn 81-year-old female with hypertension presented with progressive dyspnea. Cardiac auscultation revealed a diastolic murmur over the left sternal border. Transthoracic echocardiography demonstrated severe aortic regurgitation due to significant aortic root dilatation. Transapical TAVR was planned. Prosthetic size was determined via computed tomography. Pre-procedure transesophageal echocardiography (TEE) identified two ACTs connecting the free margin of the non-coronary cusp to the aortic sinus wall. TAVR with a self-expanding valve was performed, with intraoperative TEE confirming stable deployment despite rupture of two ACTs. The patient recovered uneventfully without perioperative complications, and follow-up transthoracic echocardiography confirmed optimal valve position with no paravalvular leakage.ConclusionACT presence does not preclude TAVR but requires meticulous intraoperative surveillance, TEE is critical for detecting these structures and guiding TAVR planning. Precise intraoperative positioning of valve graspers ensures avoidance of ACT-related complications, and rupture of ACT confirmed that it would not compromise prosthetic valve stability in the future. This case supports the feasibility of TAVR in complex aortic root anatomies with incidentally detected ACT.